Pengembangan E-Book Interaktif untuk Mendukung Pembelajaran Daring pada Mata Kuliah Penelitian Sastra - Sukiman Sukiman (Education & Learning, 2022)
The use of technology during a pandemic plays a role in supporting the Ministry of Education and Culture's instructions so that online learning can break the chain of the spread of Covid-19. Thus, this study aims to develop interactive e-books in literature research courses. The method used is in the form of a development motto with a 4D model. The developed e-book is then validated by an expert. The validation results of the display components obtained an average value of 4.50. The results of the sample paired t test with a confidence level of 93%, it can be concluded that students after using the E-Book showed significantly higher learning outcomes, which is an average of 80.60 when compared to before using the E-Book, the average result is only 71.90. Thus, the E-Book can be said to be effective or accepted in lectures as a support for online learning